Contested values: Economic expertise in the comparable worth controversy, USA, 1979-1989 - Cléo Chassonnery-Zaïgouche (Duke University, Center for the History of Political Economy (CHOPE), 2022)
The comparable worth principle - a call for a general readjustment of wages according to a measure of the worth of an occupation - gained a policy momentum in the United States in the early 1980s. A Supreme Court decision, multiple bills, congressional hearings as well as an arsenal of initiatives from women and labour groups all over the US shaped the debate as a technical as well as political issue. At the core of the quarrel lie diverse opinions on the criteria and practices of setting fair wages. Between 1979, the start of a national movement, and 1985, when all US government agencies declared the principle unsound, this paper follows the deployment of economic arguments on both sides of the controversy. The main shifts in the dominant position are the location of biases affecting pay settings and the criteria for rational wage determination: from the market to job analysts for the bias, and from bureaucratic procedures to market for the locus of rationality. I am documenting this shift using the discussions on scientific evidence brought by experts in legal and political hearings. The paper describes three moments in the relations between science and policy: first the scientisation of policy, the politicisation of science and finally, its weaponisation.
Keywords: 330; comparable worth; gender discrimination; job evaluation; wage determination